Power conversion for environment friendly electrically assisted rickshaw using photovoltaic technology in Bangladesh - Chowdhury, Shaika J.; Rahman, Rifat; Azad, Akm M. (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the IEEE Transportation Electrification Conference and Expo, ITEC 2015; Dearborn; United States; 14 June 2015 through 17 June 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http:// 10.1109/ITEC.2015.7165735